2016
DOI: 10.1007/s00439-016-1721-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing of Rett syndrome-like patients reveals the mutational diversity of the clinical phenotype

Abstract: Classical Rett syndrome (RTT) is a neurodevelopmental disorder where most of cases carry MECP2 mutations. Atypical RTT variants involve mutations in CDKL5 and FOXG1. However, a subset of RTT patients remains that do not carry any mutation in the described genes. Whole exome sequencing was carried out in a cohort of 21 female probands with clinical features overlapping with those of RTT, but without mutations in the customarily studied genes. Candidates were functionally validated by assessing the appearance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 39 publications
(53 reference statements)
3
82
0
2
Order By: Relevance
“…In one study of 21 girls with features of RTT, WES was able to identify pathogenic variants in different genes in two-thirds of the cohort. Some of these variants affected genes previously associated with neurodevelopmental phenotypes, such as HCN1 , SCN1A , TCF4 , GRIN2B , SLC6A1 , while others were in candidate genes not previously associated with neurodevelopmental disorders, such as SEMA6B [7]. In another study of 22 patients with RTT, who had prior negative clinical testing for mutations in MECP2 , CDKL5 , and FOXG1 , WES revealed likely pathogenic variants in the majority of cases, including in IQSEC2 , TCF4 , and WDR45 [10], three of the genes identified in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study of 21 girls with features of RTT, WES was able to identify pathogenic variants in different genes in two-thirds of the cohort. Some of these variants affected genes previously associated with neurodevelopmental phenotypes, such as HCN1 , SCN1A , TCF4 , GRIN2B , SLC6A1 , while others were in candidate genes not previously associated with neurodevelopmental disorders, such as SEMA6B [7]. In another study of 22 patients with RTT, who had prior negative clinical testing for mutations in MECP2 , CDKL5 , and FOXG1 , WES revealed likely pathogenic variants in the majority of cases, including in IQSEC2 , TCF4 , and WDR45 [10], three of the genes identified in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In one study that evaluated 21 females with features of RTT, two-thirds of the patients had pathogenic variants in genes other than MECP2 , CDKL5 , and FOXG1 [7]. In another study of 19 patients with features of RTT, two had pathogenic genomic imbalances, six had variants in genes already associated with neurodevelopmental disorders, and five had variants in candidate disease genes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal pads on fingers and toes, and stereotypic hand movements such as hand clapping are important features. TCF4 is the main causative gene for the classical Pitt‐Hopkins phenotype; variants in this gene have also been reported in 2 patients with a Rett‐like phenotype . In the Danish cohort, a single patient suspected of having RTT due to hyperventilation and hand stereotypies has a pathogenic TCF4 variant (Table ).…”
Section: Clinical or Genetic Diagnosis?mentioning
confidence: 99%
“…The most common genes involved apart from MECP2 are: CDKL5 (cyclin‐dependent kinase‐like 5), in which variants cause the early onset seizure disorder and FOXG1 , which is responsible for the congenital RTT variant . Several additional new genes have been suggested to be associated with atypical RTT and a Rett‐like disorder . These studies have also revealed previously unrecognized clinical similarities of Rett spectrum phenotypes with other neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, mutations in CDKL5 , SHANK3 , FOXG1 , ANKRD31 , and CHRNA5 cause a RTT-like phenotype [810]. …”
Section: Introductionmentioning
confidence: 99%